The Implementation of Educational Service Marketing (A Case Study at MAN 1 OKU Selatan) - Sahniarti; Ahmad Zainuri; Zainal Berlian (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This article discusses the educational service marketing strategy implemented by MAN 1 OKU Selatan as an effort to strengthen the image and appeal of the madrasah amidst the competition in the education sector. The madrasah promotes flagship programs such as Tahfiz, Tilawah, Digital Class, as well as academic and non-academic achievements that have reached provincial level. The research was conducted using a case study method with interviews, direct observation, and document analysis. The findings show that the marketing strategy, which focuses on promoting flagship programs, publishing achievements through social media, and offering diverse extracurricular activities such as sports, arts, and student organizations, significantly helps attract public interest. The use of digital media and good relationships with the community are key factors supporting marketing success. These results indicate the importance of an integrated approach in marketing educational services. As a recommendation, optimizing digital media and strengthening networks with alumni can further enhance the madrasah's competitiveness.